Implementasi Kebijakan Izin Reklame di Kota Denpasar - Wirmayanti, Ni Putu Ayu Kumala (CITIZEN CHARTER, 2017)
ABSTARCT Advertising Permit Policy is an effort made by the Denpasar City Government to improve the planning, implementation, guidance, control and supervision and publishing advertisements in order to realize the harmonious use of space for the installation of advertisements in the city of Denpasar. With this policy is expected able to support the effectiveness of a policy of implementing agencies, target groups and the environment, especially the community in the process of licensing advertisements in Denpasar. This research was conducted using descriptive qualitative data collection techniique in depth interview with the inforrmant. This study measures how the implementatiion of the Advertiising Perrmit Poliicy in Denpasar City by using the Implementation of Public Policy theory by George C. Edward III that based on indicator of communication, resources, dispotition and bureaucracy sstructuree. The resultss oof this sstudy iindicate the iimplementation of the policy of advertisement permit in Denpasar hass not bbeen rrunning welll because there is still often miscommunication between community / advertisement owners, clarity of policy-related information is still not optimal, thus affecting the participation of advertisers in the license process, as the lack to human resources in supervising and curbing billboards, Barriers to be addressed are communication, coordination, clear information delivery, adequate human resources and awareness raising of the importance of conducting licensing process to increase PAD through advertisement tax. Keywords : policy implementation, public policy,advertisement permit